2021
DOI: 10.1016/j.labeco.2021.102001
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Shy Away from Public Speaking? A Field Experiment

Abstract: Public speaking is an important skill for career prospects and for leadership positions, but many people tend to avoid it because it generates anxiety. We run a field experiment to analyze whether in an incentivized setting men and women show differences in their willingness to speak in public. The experiment involved more than 500 undergraduate students who could gain two points to add to the final grade of their exam by orally presenting solutions to a problem set. Students were randomly assigned to present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Finally, we turn to the question of whether public speaking aversion varies by gender (De Paola et al, 2020). Women chose minimum payments that were 1.40 Euros higher on average, a small difference that is not statistically significant (two-tailed t-test; p=0.40).…”
Section: Lab Experimentsmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, we turn to the question of whether public speaking aversion varies by gender (De Paola et al, 2020). Women chose minimum payments that were 1.40 Euros higher on average, a small difference that is not statistically significant (two-tailed t-test; p=0.40).…”
Section: Lab Experimentsmentioning
confidence: 98%
“…21 Regardless of sample choice, we always find that students in the Presentation treatment asked for a significantly higher compensation than students in the Essay treatment. In column 5, we examine whether women are more averse to giving a presentation in front of the class compared to men (De Paola et al, 2020). The coefficient estimate for the Female*Presentation interaction shows that women did not ask for a higher premium for the 19 The women who gave a presentation were not seen as more stressed than their male counterparts by audience members.…”
Section: Classroom Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the quantity of communication, observational data suggest that in public settings like academic conferences and seminars, women tend to ask fewer questions than men (Davenport et al, 2014;Hinsley et al, 2017;Carter et al, 2018;Dupas et al, 2021). This might have to do with women having a stronger aversion to speaking in public, but the experimental evidence on this question is mixed (De Paola et al, 2021;Buser and Yuan, 2022). Regarding communication behavior in small groups, studies in psychology tend to find that males dominate females in terms of speaking time (MacLaren et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence on group dynamics demonstrates that men and women do not behave similarly in group deliberations, in terms of voice and influence. For instance, women speak less than men and are considered less powerful during group deliberations (Karpowitz et al, 2012;De Paola et al, 2021). Born et al (2018) found, moreover, that women's individual decisions are less likely to be incorporated into the group's final decision.…”
mentioning
confidence: 99%